Floristic composition, life forms and phytogeography of the mountains between Damghan and Shahrud, Eastern Alborz (Iran) - Rahnama, Fateme; Naderi, Reza; Amirahmadi, Atefe (Phytotaxa, 2024)
Floristic study of the southern parts of Eastern Alborz in Iranian country was conducted. Encompassing an area of approximately 700 km², this region is located about 50 km north of Damghan and Shahrud (Semnan province), with a high difference in elevations ranging from 1400 to 3813 meters above sea level. According to 2400 collected herbarium specimens, a total of 674 taxa belonging to 332 genera and 71 families were identified. The most abundant families were Asteraceae (46 genera, 97 species), Brassicaceae (35 genera, 59 species), and Poaceae (33 genera, 65 species), respectively. The genus Astragalus, with 34 species, stands as the largest genus in the study area, followed by Cousinia (14 species), Bromus (13 species), Silene, Acantholimon, and Allium (each with 9 species), as well as Alyssum, Gagea, and Poa (each with 8 species). The flora of the study area has a significant influence of Irano-Turanian elements (369 taxa), followed by combinations of Irano-Turanian/Europe-Siberian (127 taxa), Irano-Turanian/Europe-Siberian/Mediterranean (47 taxa), Pluriregional (24 taxa), and Irano-Turanian/Saharo-Arabian elements (22 taxa), among others. Hemicryptophytes (43.62%) emerged as the most prevalent life forms in this region, followed by the others. Overall, 78 species were identified as Irano-Turanian endemics, with many facing threats due to overgrazing and the ongoing effects of climate change.